Estudo dos efeitos da restrição alimentar nas características das fibras musculares de bovinos jovens confinados - Arrigoni, Mario de Beni [UNESP]; De Figueiredo Vieira, Paulo [UNESP]; Silveira, Antonio Carlos [UNESP]; Furlan, Luiz Roberto [UNESP]; Pai, Vitalino Dal [UNESP]; Costa, Ciniro [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; De Oliveira, Henrique Nunes [UNESP] (My University, 1998)
The influence of restricting feed intake of young bulls in feedlots was evaluated in terms of structure of muscular fibers and respective areas, sampled by biopsy on the semitendinoso muscle. Sixty six crossbred Simental-Nelore bulls, 8 months old, averaging 220±34.03 kg were submited for 84 days in phase 1 (growing period), to three treatments: ad libitum (AL), restriction + whole soybean (RWS) and restriction + toasted whole soybean (RTS). The level of restriction of feed intake was 23%. Phase 2 was performed by splitting the animals in each treatment in phase 1 in two groups, feeding one with a diet containing soybeans and the other with poultry litter. The results showed that the animals AL presented more white fibers (FG), compared to the RWS and RST and a larger area of these fibers. A greater frequency of red fibers was observed in treatments RWS and RST. The conclusion was that the restriction of feed intake and consequent compensatory growth contributed for modulation of the muscular fibers increasing the frequency of the fast oxidative glycolitic (FOG) in 10.88% and decreasing of the slow oxidative (SO) and FG in 4.81 and 6.90%, respectively, with possible alteration on meat quality.

Foram avaliadas as respostas da restrição alimentar em bovinos jovens confinados quanto à composição das fibras musculares e respectivas áreas, amostradas pelo método de biópsia no músculo semitendinoso. Utilizaram-se 66 bovinos inteiros mestiços Simental - Nelore, com 8 meses e peso médio de 220±34,03 kg, submetidos a três tratamentos na fase 1 (crescimento): Ad libitum (AL); restrição + soja crua (RSC); e restrição + soja tostada (RST), com duração de 84 dias, sendo o nível de restrição em torno de 23%. A fase 2 (terminação) foi composta da divisão de cada um dos tratamentos em dois lotes: um com soja e outro com cama de frango. Os resultados mostraram que os animais do tratamento AL apresentaram maior freqüência de fibras brancas (FG), comparados aos do RSC e RST, e maior área dessas fibras. Maior freqüência de fibras vermelhas foi observada nos tratamentos RSC e RST. Concluiu-se que a restrição alimentar e conseqüente ganho compensatório favoreceu a modulação dos três tipos de fibras, aumentando a freqüência das fibras intermediárias (FOG) em 10,88%, e diminuindo as vermelhas (SO) e FG em 4,81 e 6,90%, respectivamente, com possíveis alterações na qualidade da carne.
Study of the effects of nutritional restriction on the characteristics of muscle fiber of young bulls
Keywords: Crossbred Simental-Nelore; Feedlot; Muscle fibers; Restriction of feed intake; Animalia; Glycine max